1968
DOI: 10.1037/h0025904
|View full text |Cite
|
Sign up to set email alerts
|

Altruism as a search for justice.

Abstract: 153 female undergraduates participated in 2 studies designed to investigate the effect of the desire to establish or maintain justice in a social situation (the need to believe in a just world) on altruistic behavior. In the 1st study, Ss who had experienced betrayal by 1 partner apparently attempted to identify with a more successful partner in another task. Rewarded Ss, however, made most effort to help a previously betrayed partner. In the 2nd study, when the opportunity to identify with a more successful p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…In earlier research, Lerner and colleagues (Braband & Lerner, 1975;Simmons & Lerner, 1968) have shown that participants in their studies judged the fairness of their own and others' outcomes according to whether they got what they deserved. Lerner, Miller, and Holmes (1976) note that the criteria of entitlement in such studies were the familiar "inputs" of effort, self-deprivation, relative performance or contribution that are valued in social exchanges.…”
Section: Discussionmentioning
confidence: 96%
“…In earlier research, Lerner and colleagues (Braband & Lerner, 1975;Simmons & Lerner, 1968) have shown that participants in their studies judged the fairness of their own and others' outcomes according to whether they got what they deserved. Lerner, Miller, and Holmes (1976) note that the criteria of entitlement in such studies were the familiar "inputs" of effort, self-deprivation, relative performance or contribution that are valued in social exchanges.…”
Section: Discussionmentioning
confidence: 96%
“…The data generated by Simmons and Lemer (1968) employing virtually the same situation Berkowitz and his students had used were generally supportive of the justice theory hypotheses. By and large, the subjects in this experiment were sensitive to the prior fate of the supervisor along the lines suggested by the desire to maintain justice.…”
Section: Justice Theory and A "Normative" Explanationmentioning
confidence: 96%
“…Researchers have extensively examined people's varied compensatory reactions to injustice, including victim derogation and blame (Lerner & Miller, 1978), helping (DePalma, Madey, Tillman, & Wheeler, 1999;Simmons & Lerner, 1968), and retribution (Carlsmith, Darley, & Robinson, 2002;Goldberg, Lerner, & Tetlock, 1999;Miller & Vidmar, 1981). If the death of a physically attractive person does pose a threat to observers' BJW, then one should expect, along with increased perceptions of injustice, compensatory cognitive and/or behavioral reactions aimed at ameliorating the threat (Lerner, 1980).…”
Section: Studymentioning
confidence: 97%